Expression of professional identity of IT students from the gender perspective - Stanišauskienė, Vilija; Urbonienė, Aistė (Information & Media, 2018)
The sector of IT is an exceptionally male professional area, and it is rather difficult for women to become professionals in this field. This paper aims to identify the expression level of professional identity among Lithuanian IT students from the gender perspective. Therefore, this article addresses the following research questions: what career decisions were taken when choosing studies in IT? What features describe the professional identity of IT students in different stages of its development? What factors influence the formation of the professional identity in IT from the gender perspective?The sample consisted of 100 informants (17 females and 83 males) that wrote their self-reflections under the topic “My Career.” A qualitative content analysis was used. The study revealed that female students have low levels of professional identity for IT, while male students express a mostly strong professional identity.